Tax shape, debt and electoral opportunism at the municipal level: French empirical evidence and a model - Marie-Estelle Binet; Jean-Sébastien Pentecote (European Regional Science Association (ERSA), 2003)
Firstly, this paper aims at building a theoretical framework in order to explain opportunistic local public behaviors on the eve of elections. The resulting electoral cycle depends on the tax shape, the avalability to contract loans, and the shape of the demand for public goods. In particular, the model predicts a tax cut during the election period in French municipalities. Indebtedness may lead to an electoral cycle on public spending provided that the public good demand is elastic enough. Secondly, empirical investigation relying on a dynamic panel data model confirms theoretical predictions.
Keywords: 330